2014
DOI: 10.1371/journal.pone.0089881
|View full text |Cite
|
Sign up to set email alerts
|

An Enteroendocrine Cell – Enteric Glia Connection Revealed by 3D Electron Microscopy

Abstract: The enteroendocrine cell is the cornerstone of gastrointestinal chemosensation. In the intestine and colon, this cell is stimulated by nutrients, tastants that elicit the perception of flavor, and bacterial by-products; and in response, the cell secretes hormones like cholecystokinin and peptide YY – both potent regulators of appetite. The development of transgenic mice with enteroendocrine cells expressing green fluorescent protein has allowed for the elucidation of the apical nutrient sensing mechanisms of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
177
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 207 publications
(189 citation statements)
references
References 62 publications
7
177
1
4
Order By: Relevance
“…The method allowed us to document the entire ultrastructure of an enteroendocrine cell and its neuropod. Within neuropods, we found structural features of neuronal axons, and outside neuropods, we found a physical relationship to enteric glia 8 . Indeed, neuropods contain about 70% of all secretory vesicles suggesting an essential role in the secretory function of these cells.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…The method allowed us to document the entire ultrastructure of an enteroendocrine cell and its neuropod. Within neuropods, we found structural features of neuronal axons, and outside neuropods, we found a physical relationship to enteric glia 8 . Indeed, neuropods contain about 70% of all secretory vesicles suggesting an essential role in the secretory function of these cells.…”
Section: Introductionmentioning
confidence: 71%
“…Indeed, neuropods contain about 70% of all secretory vesicles suggesting an essential role in the secretory function of these cells. Building on the structural data, more recently we found that through these neuropods, enteroendocrine cells and neurons innervating the gut form a neuroepithelial circuit, similar to that of taste cells in the tongue 8,9 .…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In some cases, however, these cells have a basal extension that extends in close apposition to neighboring epithelial cells, nerves and the processes of subepithelial enteric glial cells. 21,22 These basal processes have been termed 'neuropods' because they possess the proteins that are involved in vesicular release at synapses. 21,22 This anatomical arrangement suggests a tighter release-effector cell relationship than was previously appreciated, which allows for far more precise temporal and spatial signaling for gut peptides and their target cells.…”
Section: Ka Sharkeymentioning
confidence: 99%
“…21,22 These basal processes have been termed 'neuropods' because they possess the proteins that are involved in vesicular release at synapses. 21,22 This anatomical arrangement suggests a tighter release-effector cell relationship than was previously appreciated, which allows for far more precise temporal and spatial signaling for gut peptides and their target cells. In the case of enteric glia, this seems to be for the maintenance of epithelial barrier function.…”
Section: Ka Sharkeymentioning
confidence: 99%